Tough and biodegradable thermosets derived by blending of renewable resource based hyperbranched epoxy and hyperbranched polyester. (January 2019) - Saikia, Aditi; Hazarika, Deepshikha; Karak, Niranjan
Abstract: Renewable resource derived polymers are the most widely explored polymers from the past two decades because of their non-toxicity and environment-friendly nature. Therefore, in the present study blends from two different bio-based polymers with the special architecture, viz. hyperbranched epoxy and hyperbranched polyester were prepared by mechanical mixing at different weight ratios. The prepared blends were characterized by Fourier transform infrared spectroscopy and X-ray diffraction technique. The thermosets of these blends showed good tensile strength (14.9 MPa), elongation at break (274%), impact resistance (21.3 kJ/m 2 ), scratch resistance (up to 6.5 kg) and thermal (Onset temperature: 224 °C) properties indicating improvements in flexibility and thermostability up to an appreciable extent. The blends also showed good biodegradability when exposed to gram positive and gram negative bacterial stains. Highlights: Thermoset of bio-based hyperbranched epoxy and hyperbranched polyester, fabricated. Thermoset exhibited high elongation and impact resistance. Thermoset showed biodegradability against gram positive and negative bacteria.